Case report: Spontaneous remission in lung carcinoma with a late relapse after adjuvant immunotherapy: Exceptional tumor micro-environment - Chen, Yan; Guan, Wenhui; Zhong, Changhao; Deng, Jiaxi; Hu, Minjuan; Mo, Wenwei; Xie, Xiaohong; Li, Shiyue; Zhou, Chengzhi; Lin, Xinqing (Frontiers in Immunology, 2023)
Spontaneous remission (SR) of local recurrence after adjuvant immunotherapy has rarely been reported, and the underlying mechanism is poorly understood. Herein, we reported a patient with stage cT2aN2M0 squamous cell lung carcinoma who received neoadjuvant and adjuvant treatment with nivolumab plus chemotherapy. The patient experienced a late relapse in the subcarinal lymph node seven months after the last dosage of treatment but achieved SR in the next three months without additional antitumor therapy. The complete response lasted for eleven months and counting. Notably, high copies of pathogenic microorganisms were detected in the patient’s bronchoalveolar lavage fluid along with the recurrence but disappeared after SR. The patient also experienced a lymph node puncture-induced fever but had no other symptoms. A longitudinal analysis of infiltrated immune cells in the recurrent lymph node was performed by multiplex immunofluorescence and whole transcriptome sequencing, which revealed that CD8+ T cells were recruited during the initial relapse, specifically in the stromal area, then migrated into the tumor tissue, and continued to increase after elimination of tumor cells. Meanwhile, the initial recruitment of CD8+ T cells was coupled with a higher proportion of B cells, and the abundant neutrophil population was synchronous with the infiltration of CD8+ T cells into tumor cells. This is the first report on an NSCLC patient with a late relapse after adjuvant ICI therapy who achieved SR. Our case highlights the complexity and plasticity of antitumor immunity and is expected to help find efficient strategies against the resistance of ICI treatment.